THE INFLUENCE OF COMPENSATION, ORGANIZATION CULTURE AND MOTIVATION ON EMPLOYEE PERFORMANCE - KAREL TJAHJADI; MELIANTHA SANJUNG URIA (Media Bisnis, 2021)
The purpose of this study was to analyze and determine the effect of compensation, organizational culture and motivation on employee performance at PT. Perfect Circle Engineering. This study takes a population that is an employee at PT. Perfect Circle Engineering. The sampling method used is non-probability sampling method in the form of purposive sampling. In collecting data, researchers distributed questionnaires to respondents and the samples obtained in this study were 59 questionnaires. The tool used to analyze data is the multiple regression method. The results obtained from this study are the compensation and motivation variables individually affect the performance of employees while the organizational culture individually does not affect the performance of employees.